Reproductive characteristics of pre-pubertal bulls supplemented with vitamin A (Research, Society and Development, 2020)
Fertility is the most important factor in determining profitability of beef herd. Deficiency of vitamins and other essential nutrients can impact bull reproduction components. The aim of this study was to evaluate the reproductive characteristics of pre-pubertal bulls supplemented with vitamin A. Forty Nellore bulls aged between 18 and 20 months were used. They were allocated into two groups: treated, which received vitamin A (2 ml/animal); and control, which were not supplemented. The animals went through andrological examination. Orchiectomy was performed for histopathological evaluation of the testis. Mean motility and sperm vigor were higher in the animals present in the treated group (p